What Makes Airbnb Experiences Enjoyable? The Effects of Environmental Stimuli on Perceived Enjoyment and Repurchase Intention. (May 2021) - So, Kevin Kam Fung; Kim, Hyunsu; Oh, Haemoon
While scholarly inquiry into Airbnb has experienced an exponential growth in the tourism literature, the role of the environmental stimuli of Airbnb experiences in creating consumer enjoyment is underexplored. Adopting the Mehrabian-Russell model, this study proposes a conceptual framework to investigate the linkages between three well-documented experiential attributes of Airbnb accommodations, perceived enjoyment, and repurchase intention. The results of two separate empirical studies with recent Airbnb users consistently show significant influences of authenticity and home benefits on perceived enjoyment, which subsequently drive repurchase intention, while social interaction was not found significant. The results of the model comparison and mediation analysis also converge across the two studies, providing strong support for the mediating role of perceived enjoyment as a mechanism that underlies the relationships between the environmental stimuli and repurchase intention. The findings provide important insights into what Airbnb attributes contribute to positive emotional responses and subsequently forming favorable behavioral consequences.